2016
DOI: 10.1080/21551197.2016.1162259
|View full text |Cite
|
Sign up to set email alerts
|

Pork and Chicken Meals Similarly Impact on Cognitive Function and Strength in Community-Living Older Adults: A Pilot Study

Abstract: A pilot quasi-experimental study investigated whether provision of pork, a rich source of thiamin, as the main protein source in meals four times/week for 12 weeks resulted in improved muscle mass, body strength, and cognitive function in community-living older adults compared to similar meals containing chicken. Retirement villages were randomized to receive pre-prepared frozen meals containing either pork or chicken. Dietary intake was assessed by three-day food records and cognitive domains assessed using v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
1
18
0
2
Order By: Relevance
“…Nine intervention studies met the inclusion and exclusion criteria [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. All except one [ 41 ] were RCTs of which four included resistance exercise with nutrition intervention [ 40 , 42 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine intervention studies met the inclusion and exclusion criteria [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. All except one [ 41 ] were RCTs of which four included resistance exercise with nutrition intervention [ 40 , 42 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing full texts, one record written in Japanese, four records with overlapping studies, two ecological studies, three records with changes of brain structure or β-amyloid (Aβ) deposit as outcomes, and eight records combining meat, fish, and other food together as exposures were excluded, including one paper with an unclear description on meat by Heys et al (2010) [23] without any reply from two authors contacted. Therefore, twenty-nine eligible records were included in the review: twelve cohort [9][10][11][24][25][26][27][28][29][30][31][32], three case-control [33][34][35], thirteen cross-sectional studies [36][37][38][39][40][41][42][43][44][45][46][47][48], and one intervention study [49] (Figure 1). Egger's regression model to detect small-study effects (P < 0.05).…”
Section: Characteristics Of Studies and Quality Assessmentmentioning
confidence: 99%
“…The mean age of participants was more than 60 years except for two studies, one with a mean age of 52.9 years [46] and one with a range of 40-65 years [43]. Of twenty-nine eligible studies, twenty-four measured consumption of total meat based on a food frequency questionnaire (FFQ) and/or dietary records; one study reported consumption of beef and pork as the exposure [33]; one specified frequencies of use of red meat and sausages as the exposure [31]; two investigated whether participants had habitual intake of red meat with fat or chicken with skin (yes/no) [45,48]; and one intervention study used pork-containing meals as the exposure [49]. Among the studies included, five of them used Alzheimer's disease and/or dementia as outcomes [24,25,33,39,47], twenty-three measured cognitive function via one or a series of cognitive tests, and one reported both AD and cognitive function [31].…”
Section: Characteristics Of Studies and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations